146k views
5 votes
Perform the requested operation or operations.

f(x) = 4x + 7, g(x) = 3x2

Find (f + g)(x).

User Radames
by
6.4k points

2 Answers

1 vote
(f+g)(x) = f(x)+g(x)
4x+7 + 3x^2
(f+g)(x)= 3x²+4x+7
User Jevaughn
by
6.7k points
5 votes

Answer:

After performing the requested operation you will get
(f+g)(x)=3x^2+4x+7.

Explanation:

It is very important to take into account that the expression
(f+g)(x) is another way of writing the sum of two functions. It means that the expression
(f+g)(x) equals the expression
f(x)+g(x).


(f+g)(x)=f(x)+g(x)

Now, it's time to replace the expressions of
f(x) and
g(x) into the previous equation.


(f+g)(x)=f(x)+g(x)


(f+g)(x)=(4x+7)+(3x^2)


(f+g)(x)=3x^2+4x+7

Finally, after performing the requested operation you will get
(f+g)(x)=3x^2+4x+7.

User Shinomoto Asakura
by
6.5k points